Use of Digital Historical Material and Alternative Teaching Tools in History Lessons Project TEBIT - Berk, Neval Akça; Gültekin, Fatma; Berk, Fatih; Üstündağ, Mutlu; Güneş, Erhan; Karabağ, Gülin; Tanrıverdi, Mustafa; Uysal, Mevlüt; Kaymakcı, Selahattin; Tokdemir, Ahmet (IGI Global, 2022)
The aim of this chapter is to provide history teachers with digital historical resources and alternative teaching tools that they can use in history education in order to help students gain high-level thinking skills in addition to knowledge in history courses. To achieve this, a needs analysis for Turkish history teachers was performed to determine which subjects should be focused on in history courses, and what kind of digital historical resources and alternative teaching tools are required. The findings have shown that history teachers face difficulties in teaching ancient civilizations. Teachers have expressed that they remain abstract and incomprehensible to the students due to the inefficacy of materials and teaching tools. It has been determined that they need proper digital historical sources and alternatives most fitting for the subject at hand.
Keywords: 4. Education